Characterization of S100A12 from nile tilapia (Oreochromis niloticus) and its roles on inflammatory responses. Issue 131 (December 2022) - Chen, Junxi; Huang, Yu; Wang, Bei; Lu, Yishan; Jian, Jichang; Tang, Jufen; Cai, Jia
Abstract: S100A12 is a member of S100 proteins family that induces pro-inflammatory response via ligating with the receptor for advanced glycation end products (RAGE) and subsequent activation of intracellular signal transduction pathways. But information about fish S100A12 remain largely unclear. In this study, the S100A12 homolog (On-S100A12) was identified from Nile tilapia ( Oreochromis niloticus ). On-S100A12 was mainly expressed in liver and intestine. After Streptococcus agalactiae infection in vivo, S100A12 significantly increased in brain, intestine, liver and head kidney, suggesting S100A12 might played roles in immune response. The further in vitro experiments found that recombinant protein of S100A12 (rOn-S100A12) upregulated the expression of IL1-β, TLR2, TNF-α and inhibited the expression of IL-10, indicating On-S100A12 promoted inflammatory response and activation of M1 macrophages. The present data lay a foundation to further explore the roles of fish S100 during immune defense and will also be beneficial for better understanding of fish immune-regulatory network. Highlights: On-S100A12 was cloned and characterized. On-S100A12 were significantly induced after Streptococcus agalactiae infection in vivo. rOn-S100A12 promoted the activation of M1 macrophages in vitro.